1996
DOI: 10.1073/pnas.93.26.15233
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone-related peptide (PTHrP) regulates fetal–placental calcium transport through a receptor distinct from the PTH/PTHrP receptor

Abstract: To determine the role of PTHrP in fetal calcium metabolism, blood calcium was measured in mice homozygous (HOM) 45 Ca accumulation in HOM P THrP-ablated fetuses, but P THrP-(1-34), PTH-(1-84), and the diluent had no effect. Finally, similar studies were performed on fetal mice that lacked the PTH͞PTHrP receptor gene. Ionized calcium was significantly reduced in HOM PTH͞PTHrP receptor-ablated fetuses. However, 5 min after maternal injection of 45 Ca and 51 Cr, relative accumulation of 45 Ca was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
212
5
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(228 citation statements)
references
References 40 publications
10
212
5
1
Order By: Relevance
“…1 ]. These data demonstrate that the fetomaternal calcium gradient in these mice is established between E17 and E19, and further suggest that active transplacental calciumtransport mechanisms during this period begin to contribute significantly to maternofetal calcium flux, consistent with other studies in mice and rats (23)(24)(25)(26). In contrast, fetal blood [Ca 2+ ] in P0 was significantly lower than WT and maternal blood at both E17 and E19 (P < 0.05).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…1 ]. These data demonstrate that the fetomaternal calcium gradient in these mice is established between E17 and E19, and further suggest that active transplacental calciumtransport mechanisms during this period begin to contribute significantly to maternofetal calcium flux, consistent with other studies in mice and rats (23)(24)(25)(26). In contrast, fetal blood [Ca 2+ ] in P0 was significantly lower than WT and maternal blood at both E17 and E19 (P < 0.05).…”
Section: Resultssupporting
confidence: 67%
“…Therefore, despite the marked growth restriction of the P0 fetuses at both E17 and E19 and a reduced placental mass, skeletal hypomineralization of the P0 fetus at E17 is corrected by E19, and this is achieved by a rise in Ca J mf . Work from several species suggests that active placental calcium transport is switched on, or up-regulated, near to term, as bone mineral accretion begins (23,25,26,(40)(41)(42)(43). The capacity to raise Ca J mf in P0 indicates that the functional integrity of active calcium-transport mechanisms in P0 placentas is preserved.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have clearly documented the indispensable biological importance of PTHrP/PTH1R signaling in skeletal (11)(12)(13)(14)(15) and mammary gland (16,17) development. Additional endocrine and paracrine functions have been ascribed to the mid-region and C-terminal region (107 to 139) of the molecule (18,19). In vitro studies have indicated that PTHrP displays other functions largely relating to an intracrine signaling role in the nucleus/nucleolus (4,20,21) and that its subcellular distribution is cell-cycle dependent (22) in that PTHrP is targeted to the nucleolus of cells in G 1. In the present study, we examined the potential biological relevance of the nuclear localization of PTHrP in vivo by inserting a premature termination codon (TGA) in the murine Pthrp, and generating a ''knock-in'' (KI) mouse expressing PTHrP (1-84), a form of the protein that lacks the NLS and C-terminal region.…”
Section: Ntranuclear Transport Of Numerous Polypeptide Ligands Hasmentioning
confidence: 99%
“…44,45 During follow-up, the main determinant of plasma PTH was infant body weight, which probably reflects an increased need for calcium with skeletal growth as the infants' own parathyroid glands are taking over following birth. [46][47][48][49] However, our data do not exclude that plasma PTH per se may exert an effect on growth and body weight. Importantly, because of the design of our study, it does not allow for conclusions on cause-effect relationships.…”
Section: Maternal and Infant Vitamin D Status S Vij Streym Et Almentioning
confidence: 99%